Organizational model based on an integrated approach to encouraging students in physical education and sports activities at the university: a theoretical aspect - Kharitonov, D.A.; Ponomarev, V.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate and develop an innovative model based on a comprehensive approach to encouraging students to participate in physical education and sports activities at university and to recommend its implementation in practice. Methods and structure of the study. The study was conducted at Siberian Federal University between 2023 and 2025. It analysed mass sports and physical education and health activities among students at the university, as well as at other higher education institutions in the Krasnoyarsk Krai. Results and conclusions. Analytical and statistical work has shown low activity and participation of the region's student youth in physical education and sports events.